Linkage disequilibrium at the APA insecticidal seed protein locus of common bean (Phaseolus vulgaris L.) - Blair, Matthew W.; Prieto, S.; Díaz, Lucy Milena; Buendía Castellanos, Hector F.; Cardona Mejía, César (Springer, 2010)
Background: An interesting seed protein family with a role in preventing insect herbivory is the multi-gene, APA family encoding the ?-amylase inhibitor, phytohemagglutinin and arcelin proteins of common bean (Phaseolus vulgaris). Variability for this gene family exists and has been exploited to breed for insect resistance. For example, the arcelin locus has been successfully transferred from wild to cultivated common bean genotypes to provide resistance against the bruchid species Zabrotes subfasciatus although the process has been hampered by a lack of genetic tools for and understanding about the locus. In this study, we analyzed linkage disequilibrium (LD) between microsatellite markers at the APA locus and bruchid resistance in a germplasm survey of 105 resistant and susceptible genotypes and compared this with LD in other parts of the genome.